A time-domain implementation for the analysis of thin plates via the Boundary Element Method. (July 2022) - Esteves, Carlos L.C.S.; Daros, Carlos H.
Abstract: This work presents a direct time-domain implementation for the analysis of isotropic Kirchhoff's plates using the Boundary Element Method. The Boundary Integral Equation (BIE) was derived via the Generalized Rayleigh–Green identity and a time-dependent fundamental solution was used to obtain several kernels necessary to evaluate the BIE. A time-history-dependent marching scheme was used to assess the plate's transient response. Different time and space discretizations were equally considered within the present work.